Advances in targeting cutaneous melanoma - Kasakovski, Dimitri; Skrygan, Marina; Gambichler, Thilo; Susok, Laura (Cancers, 2021)
To date, the skin remains the most common cancer site among Caucasians in the western world. The complex, layered structure of human skin harbors a heterogenous population of specialized cells. Each cell type residing in the skin potentially gives rise to a variety of cancers, including non-melanoma skin cancer, sarcoma, and cutaneous melanoma. Cutaneous melanoma is known to exacerbate and metastasize if not detected at an early stage, with mutant melanomas tending to acquire treatment resistance over time. The intricacy of melanoma thus necessitates diverse and patient-centered targeted treatment options. In addition to classical treatment through surgical intervention and radio- or chemotherapy, several systemic and intratumoral immunomodulators, pharmacological agents (e.g., targeted therapies), and oncolytic viruses are trialed or have been recently approved. Moreover, utilizing combinations of immune checkpoint blockade with targeted, oncolytic, or anti-angiogenic approaches for patients with advanced disease progression are promising approaches currently under pre-clinical and clinical investigation. In this review, we summarize the current ‘state-of-the-art’ as well as discuss emerging agents and regimens in cutaneous melanoma treatment.